Dwa ciała poety. Eugeniusza Tkaczyszyna-Dyckiego lektura performatywna - Waligóra, Agnieszka (Przestrzenie Teorii, 2021)
Tkaczyszyn-Dycki’s poetry invariably tempts one to identify the “external” poet (author) with a textual subject, who, thanks to various literary tricks, can be called an “internal” poet. This “internal” poet does not have a purely literary or linguistic character, as he seems to be endowed with a body, biography or agency. However, these categories cannot be convincingly described using only structural tools. The paper proposes to look at the possible performativity of Tkaczyszyn-Dycki’s poetry, designed in the text itself, starting with examining the concept of trauma, which facilitates a different view of the relationship between text and “reality”, then reinterpreting the problem of subjectivity and the crucial literary “strategy”. Therefore, it is a performative reading in the sense that it will focus on what (faith, empathy, trust – and, on the contrary, distrust) Tkaczyszyn-Dycki’s work tries to convince readers to, but also on what the main intention stands for.